Resonance frequency effects of an external coil for IOP sensor applications - Hwang, Hoyong; Kang, Byungjoo; Lee, Soo Hyun; Jang, Cheol-In; Kang, Ji Yoon; Park, Changkun (TAYLOR & FRANCIS LTD, 2014)
In this study, we investigate the resonant frequency effects of an external coil for a wireless intraocular pressure (IOP) monitoring system. The phase difference of an IOP sensor is improved using the resonant frequency of the external coil. By means of phasor diagrams, we show that the phase difference is improved as the resonant frequency of the external coil approaches the resonant frequency of the IOP sensor. The IOP sensor and a multi-layered external coil are designed using microfabrication technology and an FR-4 printed circuit board, respectively. The resonant frequency of the external coil is varied using an additional capacitor and by changing the number of layers of the multi-layered inductor pattern. From the measured results, we successfully verify that the resonant frequency of the external coil improves the phase difference of the IOP sensor.
Keywords: PRESSURE; READOUT; SYSTEM